Sildenafil citrate inhibits agonist induced contractions in isolated rat seminal vesicles - Orhan, Irfan; Onur, Rahmi; Tasdemir, Cemal; Ayar, Ahmet; Kadioglu, Ates (Elsevier Science Inc, 2006)
Purpose: Sildenafil is reported to regulate smooth muscle contractility through nitric oxide-cyclic guanosine monophosphate, not only in the corpus cavernosum. Its possible effects on seminal vesicle contractility might be of importance with respect to premature ejaculation. We investigated the effects of sildenafil citrate (Pfizer, New York, New York) on agonist induced isometric contractions of the rat seminal vesicle in vitro. Materials and Methods: Seminal vesicles isolated from adult male Wistar rats were suspended in an organ bath and contracted by NE (10 mu M), ACh (10 mu M) or KCl (60 mM) (Sigma, Deisenhofen, Germany). The effects of sildenafil citrate (100 to 300 AM) were evaluated in terms of mean contraction amplitude, the area under force-time curves and isometric contractility indexes. Results: Sildenafil citrate (300 mu M) significantly inhibited the mean amplitude +/- SEM of contractile responses induced by NE (1,061 +/- 153 vs 271 +/- 65 mg, p < 0.0001), ACh (475 +/- 51 vs 68 +/- 17 mg, p < 0.0001) and KCl (546 +/- 71 vs 59 +/- 18 mg, p < 0.0002). It also caused dose dependent concomitant decreases in the area under force-time curves. Additionally, pretreatment with sildenafil citrate markedly prevented the contractile response to NE, ACh and KCl. Conclusions: Our results indicate that sildenafil citrate inhibits the contractions of isolated rat seminal vesicle that are induced by NE, ACh or KCl. Future studies may support an in vivo effect of sildenafil for delaying or inhibiting seminal vesicle emission, thereby, promoting improvement in patients with premature ejaculation.
100th Annual Meeting of the American-Urological-Association -- MAY 21-26, 2005 -- San Antonio, TX
Keywords: muscle contraction; seminal uesicles; testis; sildenafil; rats; Wistar